9. EFFECTS OF GLYCEMIC REGULATION AND ACETYLCHOLINESTERASE INHIBITION OF SCORPION TURMERIC (CURCUMA RANGJUED) IN CENTRAL HIGHLANDS, VIETNAM (Vietnam Journal of Community Medicine, 2024)
Scorpion turmeric has been traditionally grown in the Central Highlands provinces of Vietnam. Prepared medicinal products from this species (Curcuma rangjued) are currently used in folk medicine to treat various illnesses including bronchitis, asthma, gastritis, and typically used as an antiseptic. Despite its popular use, scientific studies into its pharmacological properties remain limited. Chemical analysis has revealed the presence of many valuable bioactive ingredients such as D-limonene, β-pinene, and caryophyllene, which exhibit high pharmaceutical potential due to antioxidant and anti-inflammatory activities (Athanasaki et al., 2022). Therefore, exploiting the medicinal resource from the scorpion turmeric plant will bring various benefits to community health care.Objectives: This study aimed to evaluate the glycemic regulation and acetylcholinesterase (AChE) inhibitory effects of the scorpion turmeric’s rhizome extracts.Methods: Blood glucose levels were measured using the method described by Sivalingam (2013), while AChE inhibitory activity was determined according to the method of Ellman et al. (1961).Results: The results have shown that scorpion turmeric’s rhizome extracts which contain D-limonene, β-pinene and caryophyllene, demonstrated significant anti-inflammatory properties. Moreover, they exhibited both in vitro and in vivo glycemic regulatory effects and inhibited AChE activity in vitro.Conclusion: The findings of this study suggest that C. rangjued possess considerable therapeutic potential for the management of diabetes and Alzheimer's disease. Therefore, the scorpion turmeric plant should be given more attention and developed to preserve this valuable medicinal resource.
Keywords: Diabetes; Alzheimer; AchE; Curcuma rangjued; Scorpion turmeric